How low can you go? Severe hyponatremia with a sodium of 94 mg/dL corrected with proactive strategy - Manan Shah; Viralkumar Amrutiya; Nikesh Patel; Sophia Kwon; Jeffrey Fein; Abraham Lo (Greater Baltimore Medical Center, 2020)
We present a case of severe symptomatic hyponatremia (94 mEq/L) in a male patient who presented with nausea, vomiting, and multiple falls. The patient was found with symptomatic hypo-osmolar hypovolemic hyponatremia secondary to volume loss from vomiting, diuretic use, and consumption of solute-free water. To manage such a severely hyponatremic patient, concomitant 3% hypertonic saline and DDAVP were initiated with successful slow and sustained correction of sodium without complications of osmotic demyelination syndrome.